Nigral iron deposition in common tremor disorders. Issue 1 (10th December 2018) - Homayoon, Nina; Pirpamer, Lukas; Franthal, Sebastian; Katschnig‐Winter, Petra; Kögl, Mariella; Seiler, Stephan; Wenzel, Karoline; Hofer, Edith; Deutschmann, Hannes; Fazekas, Franz; Langkammer, Christian; Ropele, Stefan; et al.
ABSTRACT: Objective: We investigated R2* relaxation rates as a marker of iron content in the substantia nigra in patients with common tremor disorders and explored their diagnostic properties. Methods: Mean nigral R2* rates were measured in 40 patients with tremor‐dominant Parkinson's disease (PD), 15 with tremor in dystonia, 25 with essential tremor, and 25 healthy controls. Results: Tremor‐dominant PD patients had significantly higher nigral R2* values (34.1 ± 5.7) than those with tremor in dystonia (30.0 ± 3.9), essential tremor (30.6 ± 4.8), and controls (30.0 ± 2.8). An R2* threshold of 31.15 separated tremor‐dominant PD from controls with a sensitivity and specificity of 67.5% and 72%. The sensitivity and specificity for discrimination between PD and non‐PD tremor patients was 67.5% and 60%. Conclusion: Iron content in the substantia nigra is significantly higher in tremor‐dominant PD than in tremor in dystonia, essential tremor, and controls. Because of the considerable overlap, nigral R2* cannot be suggested as a useful diagnostic tool. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.